Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.sleep.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype, social jet lag, sleep debt and food timing in inflammatory bowel disease

Abstract: The preference of the sleep/wake cycle can be grouped into categories or chronotypes. Inflammatory bowel disease (IBD) has been linked to poor sleep quality which correlates with disease severity. Social jet lag (SJL) is the difference between sleep timing on work and free days and is a marker for circadian misalignment which has been linked to increased inflammation. We investigated whether chronotype, SJL, sleep debt (SD), and food timing were associated with an IBD specific complications and a lower quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 68 publications
1
37
0
2
Order By: Relevance
“…Animal studies showed that sleep disorders promoted colonic inflammation and worsened the severity of colitis ( Preuss et al, 2008 ; Tang et al, 2009 ). Clinical studies showed a correlation of sleep disorders with IBD, in which a significant decrease in sleeping time and sleeping efficiency was closely related to the development and disease activity of IBD ( Chakradeo et al, 2018 ; Chrobak et al, 2018 ; Jarasvaraparn et al, 2019 ; Marinelli et al, 2020 ). A recent systematic review and meta-analysis confirmed the association between poor sleep quality and increased risk of IBD activity ( Hao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies showed that sleep disorders promoted colonic inflammation and worsened the severity of colitis ( Preuss et al, 2008 ; Tang et al, 2009 ). Clinical studies showed a correlation of sleep disorders with IBD, in which a significant decrease in sleeping time and sleeping efficiency was closely related to the development and disease activity of IBD ( Chakradeo et al, 2018 ; Chrobak et al, 2018 ; Jarasvaraparn et al, 2019 ; Marinelli et al, 2020 ). A recent systematic review and meta-analysis confirmed the association between poor sleep quality and increased risk of IBD activity ( Hao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported on energy intake as obtained through snacks (29,31) and during dinner (24,29,31); however, measurement times were so heterogeneous that it was not possible to draw any conclusions in this regard. It is important to point out that alterations in meal timing have been associated with inflammatory markers and changes in body weight (9,19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is necessary to know if the increase in energy intake is related to a specific meal timing. Breakfast irregularity, for example, has been associated with inflammation and change in body weight (19). Nutritional strategies can be implemented focused on the meal of greater intake and, thus, prevent weight gain in a population exposed to a short night's sleep.…”
Section: Introductionmentioning
confidence: 99%
“…However, a polymorphism in the molecular circadian clock gene Per3 is associated with increased use of immunosuppressive drugs and stricturing/fistulizing phenotype in CD [123]. In addition, some IBD patients, especially those with CD, have evidence of circadian disruption and social jet lag that is associated with a more aggressive CD phenotype (fistulizing/stricturing) [124,125]. While there are data to support that IBD patients have circadian rhythm disruption, additional studies are needed.…”
Section: (33) Peptic Ulcermentioning
confidence: 99%